(untitled) (Dhaka University Journal of Biological Sciences, 2024)
The utilization of organic fertilizers is currently on the rise to sustain higher food quality while minimizing environmental pollution. Mulching with organic materials maintains soil physical conditions, crucial for realizing a crop’s genetic yield potential even when all other requirements are met. Hence, a field experiment was conducted to investigate the effects of mustard oil cake (MOC), poultry manure (PM) and vermicompost (V) alone and in combination with mulching (Mu) on growth and yield parameters of Tomato. Significant increases were (p ≤ 0.05) observed in plant height, leaf number, leaf area, stem girth, root length and root girth of tomato plants compared to the control (T1), where no fertilizers were applied. At 90 days after transplantation (DAT), the T9 (V8Mu0) treatment resulted in the highest plant height (142 cm) and the longest root length (25 cm) while the maximum quantity of fresh weight (154.63 g plant-1) for tomato plant was obtained from the treatment T6, which received vermicompost at 4 t ha-1 with mulching. Application of poultry manure at the rate of 8 t ha-1 without mulching (T8) resulted in a significant higher number (14 fruits plant-1) of green tomatoes. Fresh weight of green tomatoes were varied significantly (p ≤ 0.05) among the treatments with the maximum fresh weight obtained from the T₉ (128.97 g plant-1) and the minimum from T₁ (12.73 g plant-1) treatments. Nitrogen, P, K, Ca, Mg and S of green tomatoes varied significantly among the treatments. The utmost P, K, S, Ca and Mg contents (0.72, 6.26, 0.23, 0.54 and 0.31 g kg-1, respectively) of green tomatoes were recorded in the treatment T₆ (V₄Mu). Hence, the utilization of organic fertilizers, either alone or in conjunction with mulching, markedly enhanced the growth and yield of the tested vegetable, offering viable strategies for enhancing the yield potential. Dhaka Univ. J. Biol. Sci. 33(2): 53-65, 2024 (July)